Bosnia and Herzegovina : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to assist the Ministry of Finance of the Republic of Srpska (RS), Bosnia and Herzegovina, in the compilation and dissemination of government finance statistics in accordance with the guidelines of the Government Finance Statistics Manual 2014 (GFSM 2014) and the European System of Accounts (ESA 2010). It was found that the chart of accounts used by the RS is very comprehensive and facilitates the bridging of the national codes to GFSM 2014 and ESA 2010 codes. Some amendments and extensions may be performed to further improve the bridging to GFSM 2014 and ESA 2010.